A comparative analysis of public administration education in the United States and post-Soviet Central Asia. (2nd January 2018) - Rauhaus, Beth M.; Sakiev, Azamat
ABSTRACT: In democracies, the importance of public service is taught in the public administration curriculum, with an emphasis on democratic governance and how administering public goods contribute to a democratic society. This comparative work contributes to the field of study by applying theories of democratic values of public administration to the process of democratization. The study focuses on a comparative study of graduate-level curriculum delivery in the United States and public administration schools in post-Soviet Central Asia (primarily in Kazakhstan and Kyrgyz Republic) governments. This work explores the curricula of public administration institutes under the Presidents of the Republic of Kazakhstan and Kyrgyz Republic. The curriculum, which tends to be controlled by the regime transitioning to democracy, prepares future public servants for state management.